PENINGKATAN STATUS GIZI BALITA STUNTING MELALUI PRAKTEK PEMBUATAN MPASI DENGAN MEMANFAATKAN POTENSI PANGAN LOKAL - Ayu Wulandari; Devi Valeriani; Dian Prihardini Wibawa; Kamalia Layal (Jurnal Abdi Insani, 2023)
The 2023 University Level Community Service Program aims to increase knowledge, understanding, and skills in the practice of making MPASI by utilizing local potential for mothers who have babies, toddlers, toddlers and toddlers so they have good nutritional intake. This was done as a way to prevent stunting in Simpang Teritip District, West Bangka Regency. Considering that this area is one of the locations with a high stunting prevalence rate in the Bangka Belitung Islands Province. The activities carried out in this service are in the form of outreach and education with the theme of nutritious food and direct practice in making complementary foods. This activity is carried out by utilizing existing local food. The hope is that eventually parents can implement in their daily life the fulfillment of the right MPASI for their children.